2020
DOI: 10.1039/d0ma00293c
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic conversion of CO2 to chemicals and fuels: the collective thermocatalytic/photocatalytic/electrocatalytic approach with graphitic carbon nitride

Abstract: Carbon nitride with tunable textural properties, chemical properties (N contents, types of N species, and dopants), and optoelectronic properties can activate and convert CO2 to useful chemicals and fuels by using various forms of energy resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(64 citation statements)
references
References 214 publications
(229 reference statements)
0
62
0
Order By: Relevance
“…Carbon dioxide is one important contributor to the greenhouse effect, and its increasing emission from various sources triggers research of its capture and recycling into chemicals. [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ] The use of CO 2 , which is non‐toxic and abundantly present in nature, as a C1 building block in chemical reaction systems is still not very common due to its high thermodynamic and kinetic stability. [14] However, despite this, there are systems which are known to show reactivity towards CO 2 .…”
mentioning
confidence: 99%
“…Carbon dioxide is one important contributor to the greenhouse effect, and its increasing emission from various sources triggers research of its capture and recycling into chemicals. [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ] The use of CO 2 , which is non‐toxic and abundantly present in nature, as a C1 building block in chemical reaction systems is still not very common due to its high thermodynamic and kinetic stability. [14] However, despite this, there are systems which are known to show reactivity towards CO 2 .…”
mentioning
confidence: 99%
“…Meanwhile, Wang et al found that the production of CH 3 OH and CH 4 on C 3 N 5 was kinetically favorable through the COOH* reduction pathway on the N atoms in the NN linkage between the heptazine framework 40 . The adsorption strength of CO on the catalyst surface also plays a key role in influencing the product selectivity as a weak CO adsorption results in the easy desorption of CO as an exclusive reduction product, 72 thereby stifling the possibility of further intermediates and product varieties to be formed. The diversity that can exist among varying structures, allotropes, and modifications of the carbon nitride surface shows that the specific reduction pathway is unique to the local surface chemistry and crystallinity of the catalyst surface.…”
Section: Principle Of Photocatalytic Co2 Reduction On Carbon Nitridementioning
confidence: 99%
“…Meanwhile, the external bias provided by the electrical energy can significantly reduce the charge recombination during the CO 2 reduction process, thus increasing the stability of the photocatalyst 334 . Other external factors governing the activity of photoelectrocatalysis are also essential to improve the efficiency of CO 2 RR, including the pH and type of electrolyte, pH changes during long‐term cycling, operating conditions (gas/liquid phase), and CO 2 pressure 72,335 . For example, a high local pH at the electrode/electrolyte interface suppresses the HER and CH 4 to favor multi‐carbon products, while the preparation of thin film electrodes aids in decreasing the mass transfer resistance, effectively promoting the light‐driven CO 2 reduction reaction 336 .…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…The utilization of CO 2 to produce valuable compounds, especially fuels, is one of the thrust research areas of the present time, which could counter serious environmental challenges and act as a clean energy provider. 5 Moreover, the strategic utilization of CO 2 to produce valuable chemicals and fuels could be a potential tool for carbon neutrality in order to minimize carbon emissions. There are many possible methods, including thermal conversion, electrochemical conversion, photochemical conversion, and biological transformation of CO 2 into chemicals and fuels.…”
Section: Introductionmentioning
confidence: 99%